Flow-through anastomosis using a T-shaped vascular pedicle for gracilis functioning free muscle transplantation in brachial plexus injury (Clinics, 2015)
OBJECTIVE: In gracilis functioning free muscle transplantation, the limited caliber of the dominant vascular pedicle increases the complexity of the anastomosis and the risk of vascular compromise. The purpose of this study was to characterize the results of using a T-shaped vascular pedicle for flow-through anastomosis in gracilis functioning free muscle transplantation for brachial plexus injury. METHODS: The outcomes of patients with brachial plexus injury who received gracilis functioning free muscle transplantation with either conventional end-to-end anastomosis or flow-through anastomosis from 2005 to 2013 were retrospectively compared. In the flow-through group, the pedicle comprised a segment of the profunda femoris and the nutrient artery of the gracilis. The recipient artery was interposed by the T-shaped pedicle. RESULTS: A total of 46 patients received flow-through anastomosis, and 25 patients received conventional end-to-end anastomosis. The surgical time was similar between the groups. The diameter of the arterial anastomosis in the flow-through group was significantly larger than that in the end-to-end group (3.87 mm vs. 2.06 mm, respectively, p